Transgender Hearing and Healing: The Musical Processing of Trauma in Boys Don’t Cry and The Brandon Teena Story - Susanna Välimäki (The International Centre for Music Studies at Newcastle University, 2025)
In this article I discuss the music of two films that have significantly influenced how the story of a famous victim of an anti-transgender hate crime, Brandon Teena, has circulated, both in mainstream and transgender culture: the Oscar-winning drama film Boys Don’t Cry (dir. Kimberly Peirce, USA, 1999), and the low-budget documentary The Brandon Teena Story (dir. Susan Muska & Greta Olafsdottir, USA, 1998). Boys Don’t Cry drew in significant ways on  The Brandon Teena Story, and both are early representatives of mainstream transgender films that endeavour to communicate transgenderness in a serious manner to a larger audience.
Although these films have been frequently discussed in queer and transgender studies, the role of the music in the films has been relatively untouched. Yet film itself is a sonic art form, and audiovisual effects involving music are among the most powerful technologies for portraying gender. Furthermore, music is an especially capable vehicle for processing collective traumas, such as soci(et)al oppression and hate-motivated violence. In the present article I am interested in the musical means by which Boys Don’t Cry and The Brandon Teena Story convey the story of Brandon Teena and handle anti-transgender violence. More specifically, by drawing on transgender musicology, cultural film music research and cultural trauma studies, I will focus on how the films communicate transgender subjectivity and narrate the traumatic subject matter via music. I will also discuss the affinities and differences in the musical approaches of these films.
-